Peningkatan Pemahaman Kaidah Gramatikal (Qowa'id) Menggunakan Metode Audiolingual dengan Media Lagu Pada Pembelajaran Bahasa Arab - agni; iman; Yufi (Yayasan Al-Afif, 2024)
Abstrak The common issues in Arabic language learning are linguistic problems (such as pronunciation, rules, grammar, vocabulary, and structures) and non-linguistic problems, including motivation and interest, methods used, and language environment. The aim of this research is to investigate the Arabic language learning process at MAN 1 Garut, the planning and implementation of audiolingual method using songs as media in Arabic language learning at MAN 1 Garut, and its effectiveness in enhancing grammatical rules (qowa'id) comprehension at MAN 1 Garut. This research is a qualitative descriptive analysis. Data collection methods include observation, interviews, and documentation. Data analysis techniques involve data reduction, data presentation, and conclusion drawing. The results indicate that: (1) The curriculum used at MAN 1 Garut includes the 2013 curriculum and the independent curriculum. Teachers employ various methods and media such as audiolingual method, direct method, eclectic method, lecture method, discussion method, and assignments. Student participation and interest in Arabic language learning vary, affecting their understanding of grammatical rules and Arabic language skills, due to differences in students' backgrounds. (2) The implementation of audiolingual method with song media adheres to the steps outlined in theory. The teaching technique employed is deductive. (3) Audiolingual method with song media in Arabic language learning is effective in enhancing grammatical rules (qowa'id) comprehension, as evidenced by interviews with several 11th-grade students stating that they find it easier to understand grammatical rules after using the audiolingual method with song media.